2019
DOI: 10.2196/10208
|View full text |Cite
|
Sign up to set email alerts
|

Experiences With Video Consultations in Specialized Palliative Home-Care: Qualitative Study of Patient and Relative Perspectives

Abstract: Background The work of specialized palliative care (SPC) teams is often challenged by substantial amounts of time spent driving to and from patients’ homes and long distances between the patients and the hospitals. Objective Video consultations may be a solution for real-time SPC at home. The aim of this study was to explore the use of video consultations, experienced by patients and their relatives, as part of SPC at home. Methods This explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 20 publications
7
95
0
1
Order By: Relevance
“…The bene ts of eHealth can be increased access to care, increased convenience, reduced travel time and reduced risk of infections (47,48). These aspects are re ected in the results of this review, and in line with previous ndings from Pinto et al (19).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The bene ts of eHealth can be increased access to care, increased convenience, reduced travel time and reduced risk of infections (47,48). These aspects are re ected in the results of this review, and in line with previous ndings from Pinto et al (19).…”
Section: Discussionsupporting
confidence: 83%
“…Communication between patient, close relatives and team members was facilitated through eHealth, and patients' experienced increased access to care since physical distance was not an issue. Patients found that the use of video consultation, strengthened communication since visual features are included, also described in other studies (48,49). Another bene t found in our review was that despite life-threatening illness and being close to the end of life, patients could take an active role and govern their own care if they want to, thus promoting individualized care.…”
Section: Discussionsupporting
confidence: 68%
“…All the participants had the first contact with the SPCT face-to-face. This is in accordance with other studies that assume, that the first contact has to be face-to-face to ensure the trust of the patients and their relatives and obtain informed consent for using telemedicine [8,20]. This is in line with standard practical and ethical conduct in palliative care and the need for an initial assessment of the patient and his needs including a physical examination.…”
Section: Discussionsupporting
confidence: 86%
“…Findings from Scotland have shown that both patients and carers appreciate telehealth as an addition to clinical care [21]. Telemedicine is applicable and feasible in a Danish context [9,10,20]. Current reviews from Denmark conclude that telemedicine is useful in palliative care for communication between the SPCT and patients and relatives and that telemedicine is useful in teaching district nurses [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The study is a part of a larger qualitative study exploring patients, their relatives and healthcare professionals' experiences of using video consultations in SPC. A publication of the patients and their relatives' experiences in video consultations in SPC has been published in JMIR Journal of Medical Internet Research (Funderskov et al, ).…”
Section: Methodsmentioning
confidence: 99%